Interactive simulation of flames - Tay, Tze Yang (Universiti Malaysia Sabah, 2012)
Computer simulation is an abstract model being simulated by computer program on particular features and dynamic aspects.In particular, flame simulation is widely employed in motion pictures, computer games and virtual reality applications. The main goal of this project is to integrate an interactive flame simulation by using the Stable Fluids technique based on three gas system. The combustion process is involved along with the heat generated to drive the flow of the hot air. Physically based simulation conducted at an interactive rate enables the user to test the interactions and changesof the conditions during the simulation. The results show that the flames integration is quite constant. Any changes inflame simulationwill affectthe numberof frames persecond.The project also contains experimental results for systems with simulated physics.From theconducted experiments, the prototype of flamessimulationisdeveloped using stable fluids method.Several experiments such as frame per second areperformed to calculate the key frame. In the flame simulation, a very simple flame model is used to achieve interactive rates (10 fps on a 3.8 GHz P-IV) on very simple scenes (one flame source and wood pieces). Increasing either scene size or scene complexity will reduce interactivity. Furthermore, physical memory usage average 3,897,367 KB is used to run the simulation. The comparison of memory usage between with simulation and without simulation has shown the average differences on physical memory indicated by 8163.67KB.